Don't worry, it's safe to eat : the true story of GM food, BSE, & Foot and Mouth - Rowell, Andrew (Earthscan Publications, 2003)
An investigation of science, politics and our food production system, this text exposes the bogus science, political interference and flawed policies that threaten our food supply. The author tells the story of BSE, revealing how top scientists have been muzzled and how the epidemic continues. Then, against a backdrop of burning cows, Andrew Rowell exposes how trade and macro-economic policies overruled good science in the foot and mouth catastrophe. He also opens the black box of the so-called GM revolution to expose the myth behind the marketing. In tracing how critics are silenced in the bo.